Refractory Bilateral Contact Lens–associated Fungal Keratitis Managed with Intrastromal and Intracameral Therapy: A Case Report - Tahmina Sajjad, Muhammad Rashid, Shahid Abbas Kulachi, Muhammad Ahmad Shabbir, (Pakistan Journal of Medical & Health Sciences, 2023)
Case presentation: We report a rare case of bilateral contact lens–associated infectious keratitis in an 18-year-old female who presented with pain, redness, photophobia, discharge, and profound visual loss in both eyes. Prior to presentation, she had been treated with topical steroid-containing eye drops, following which her symptoms worsened significantly. Ocular examination revealed bilateral corneal stromal infiltrates with epithelial defects, endothelial plaques, recurrent hypopyon, and elevated intraocular pressure. Despite aggressive medical management, including topical and systemic antimicrobial therapy, repeated anterior chamber washouts, and intrastromal and intracameral antibiotic and antifungal injections, the disease demonstrated a refractory course. Progressive corneal thinning led to bilateral descemetocele formation, necessitating bilateral amniotic membrane transplantation with tarsorrhaphy. After stabilization, therapeutic keratoplasty was ultimately required in the left eye. This case highlights the potential for rapid bilateral progression of contact lens–associated keratitis, the adverse impact of prior corticosteroid use, and the need for early recognition, prompt escalation of therapy, and timely surgical intervention in severe cases to preserve ocular integrity and optimize visual outcomes. Keywords: Keratitis, Contact Lenses, Steroids, Antifungal Agents.